Non-perturbative renormalization by decoupling - Mattia Dalla Brida (Physics Letters B, 2020)
We propose a new strategy for the determination of the QCD coupling. It relies on a coupling computed in QCD with Nf≥3 degenerate heavy quarks at a low energy scale μdec, together with a non-perturbative determination of the ratio Λ/μdec in the pure gauge theory. We explore this idea using a finite volume renormalization scheme for the case of Nf=3 QCD, demonstrating that a precise value of the strong coupling αs can be obtained. The idea is quite general and can be applied to solve other renormalization problems, using finite or infinite volume intermediate renormalization schemes.